New Models of Hybrid Leadership in Global Higher Education - Donna C. Tonini; Nicholas C. Burbules; C. K. Gunsalus (Educational Considerations, 2016)
This manuscript highlights the development of a leadership preparation program known as the Nanyang Technological University Leadership Academy (NTULA), exploring the leadership challenges unique to a university undergoing rapid growth in a highly multicultural context, and the hybrid model of leadership it developed in response to globalization. It asks the research question of how the university adapted to a period of accelerated growth and transition by adopting a hybrid approach to academic leadership. The paper uses qualitative methodology to review NTULA’s first cohort, including interviews and participant survey responses. The findings illuminate three key areas of the hybridized leadership model that are challenging to balance, including managing the transition from the leadership style required to drive rapid institutional change to the approach needed to preserve that growth, how leaders reconcile the need to be responsive to both administration and faculty, and how to lead in a highly diverse, multicultural space.
Keywords: Global Higher Education; Nanyang Technological University (NTU); leadership style; new models; research-intensive; Literature and Data; Globalization; literature review; academic; policies; participants; evaluation; traits